Review of Sharia Economic Law on the Practice of Buying and Selling Non-Fungible Tokens That Others Represent Property Rights in the Curate Application - Khoirul Umam; M. Ridlwan Hambali; Dery Ariswanto (Universitas Trunojoyo Madura, 2025)
Curate is one of the buying and selling applications for non-fungible tokens that is popular among non-fungible token artist lovers. The shortcomings contained in the Curate application are used by unscrupulous application users to sell non-fungible tokens, which, of course, can harm others. The purpose of this research is to find out the practice of selling non-fungible tokens not belonging to the Online Market Curate and the review of sharia economic law on the sale of non-fungible tokens not belonging to the Online Market Curate. This type of research is field research. Sources of data in this study include primary data derived from interviews and observations, while secondary data comes from books, fiqh books, journals, and the internet. The data collection method of this research was obtained from interviews, observations, and documentation. The data obtained is processed using a descriptive analytical method using a qualitative approach based on sharia economic law theory. Based on the results of the study, it can be concluded that the motive for selling non-owned non-fungible tokens is based on the absence of strict regulations and the absence of sanctions given. The review of sharia economic law on the sale of non-owned non-fungible tokens on the Curate Online Market is prohibited sales because it does not meet the terms and conditions of bai', namely the item has a status in ownership other than the seller, as well as prohibited sales because there are other factors that harm the parties involved, namely selling booty or stolen goods.